التحولات الجديدة في آليات الاتصال السياسي في البيئة الرقمية: الدعاية والتسويق السياسي المبني على تحليل البيانات والاستهداف الدقيق للجمهور - حسان، يسرا حسني عبدالخالق (جامعة القاهرة - كلية الإعلام - مركز بحوث الرأي العام, 2021)
تهدف هذه الدراسة إلى استكشاف التحولات الجديدة في آليات الاتصال السياسي في البيئة الرقمية من خلال رصد الجديد بمجال تحليل البيانات والاستهداف السياسي الدقيق للجمهور Political Micro-Targeting، بالاعتماد على منهجية تحليلية تركز على رصد عمق التحول في آليات الاتصال السياسي، ورصد الممارسات الحديثة في الحملات السياسية بالتجربة الأمريكية والأوربية في بيئة الإعلام الرقمي واستشراف آفاق ممارستها في التجربة المصرية، والتي مثلت فيها التغيرات في بيئة الاتصالات السياسية تطورا في توظيف استخدامات الوسائل الاتصالية المختلفة، إلى طريقة متكاملة لإدارة السياسة. توصلت الدراسة لعدد من النتائج منها، أن السياسات والاستراتيجيات الاتصالية في المجال السياسي طورت كثيرا من الأدوات والمناهج باستحداثها استراتيجيات الاستهداف الدقيق ""Micro- Targeting""، وكذلك Advanced Audience Segmentation أو التقسيم المتقدم والدقيق للجمهور المستهدف، كذلك لم يقتصر الأمر في مجال الحملات السياسية الأمريكية، وتقنياتها، على مجالات استخدام الشبكات الاجتماعية وتوظيفها، إلا أن الاهتمام بدأ يتزايد كذلك بتطوير البرمجيات والتطبيقات التي لديها القدرة على تحليل البيانات في كلا الاتجاهين، الأول- قواعد معلومات الناخبين، والثاني- البيانات المتحصل عليها من خلال الأجهزة الذكية""Mobile Environment""، وبالنسبة لمجال الحملات السياسية في أوروبا هناك زيادة في استخدام نفس نهج ممارسات تحليل البيانات والاستهداف السياسي الدقيق للجمهور كما بالتجربة الأمريكية، إلا أن ما يعيق الممارسات السياسية في أوروبا، وجود بعض العوائق على رأسها قوانين حماية البيانات، والتي تمنع استخدام السياسيين لبيانات الناخبين، حيث إن التوسع في هذا الاستخدام، والتعرض لبيانات الناخبين بهذه الدقة والتحليل يتعارض مع حرية الناخبين، ويعد بمثابة اقتحام من السياسيين لخصوصية الأفراد، وبالنسبة للحملات السياسية التي تقوم بها الأحزاب المصرية وممارستها في بيئة الإعلام الرقمي يمكن القول إنها مازالت تفتقر إلى استثمار التطور التكنولوجي في مجال الإعلام الإلكتروني بالآليات التي وصلت إليها كل من التجربة السياسية الأمريكية والأوربية."
This study aims to explore the new shifts in the political communication mechanisms in the digital media environment, through an analytical methodology focused on monitoring the depth of the shift in the mechanisms of political communication, and monitoring modern trends in political propaganda practices in the American and European experience in the digital media environment, in which changes in the political communication environment represented a development in the use of different means of communication, to an integrated way of managing politics. Study found a number of results, including, modern trends in the field of American political propaganda based on a new approach to the so-called ""Data Driven Data"" (Data Driven),combined with micro-targeting techniques, the policies and strategies of the media in the political field have developed many tools and approaches by developing strategies ""Micro-Targeting"", as well as Advanced Audience Segmentation or advanced and precise division of the target audience, which played the most prominent role in allowing President Barack Obama to win the presidential election for a second term in the White House, This approach to political propaganda for American candidates has also been adopted in the field of U.S. political propaganda and its techniques, not only in the areas of the use and employment of social networks, and for those who benefit from them more quickly with the ability to communicate and target the electorate specifically and accurately, but interest is also increasing in the development of software and applications that have the ability to analyze data in both directions, first- voter information bases, and second- data obtained through mobile environment, and for the field of advertising and campaigns. In Europe, there is an increase in the use of the same approach to American political propaganda practices, but what hinders political propaganda practices in Europe, the existence of some obstacles, chief among them data protection laws, which prevents the use of voters' data, and considers that the expansion of this use, and exposure to voter data with such accuracy and analysis is contrary to the freedom of voters, and is a intrusion by politicians to the privacy of individuals."
Keywords: علوم الإعلام والاتصال -- الاتصال السياسي -- التسويق السياسي -- الاتصال الجماهيري -- الإعلام الرقمي